(3GdedNU aj GdefWbs - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s ((3eOjfI OeTb s)
(3ChdgG (B:s
(3GeG HYO ef jSJMb GdMeO dhLhH hLhOg aEf CLd eG jSeh Gdjg GYfGb GdUQGFe eYQaI GdehLhOGJ HCLfGSgG hCfhGYgG s
(3BNQgG (B:s
(3hCfg JYGdi dG jSCd YeG jaYd hgh GdMb GdeHjf hGdOjf GdeJjf hdjcf gPG BNQ cdGefG ai gPg GdeSCdI hHg Je GdcJGH s
(3GdfSNI HgG MhGTs
(3fSNI fajSI LOkGs
(3HChdg GdYOjO ef GdJedcGJ GcedJ GdcdeJ GdeWehSI Hbde eZGjQ s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdadSaI hGdefWbs